Patient outcomes, system challenges and solutions in inter-hospital transfer for acute surgical care – a literature review - Zalums, Alexandra Z. (International Surgery Journal, 2025)
Interhospital transfer (IHT) is essential for providing timely access to specialist surgical care, particularly in geographically dispersed health systems yet is consistently associated with increased morbidity, mortality, and healthcare resource use. This review synthesises contemporary evidence on IHT, outlining key challenges and proposed strategies for improvement. A literature search of MEDLINE and PubMed was conducted using predefined search terms, limited to English-language articles published within the past 10 years and involving adults aged >16 years. Relevant studies examining IHT processes, outcomes, delays and mitigation strategies were reviewed and synthesised narratively. IHT frequently occurs due to deficits in local resources, acuity capability, or specialist expertise. Across studies, transferred surgical patients experience longer hospital stays, higher costs, and significantly increased mortality, with up to threefold higher in-hospital mortality compared with directly admitted patients. Major contributors to adverse outcomes include systemic delays, inadequate communication and handover, limited specialist availability in regional hospitals, and logistical constraints. Time-critical subspecialities are particularly vulnerable to transfer-related delays, which strongly predict mortality and cost escalation. Up to 20-30% of transfers may be clinically unnecessary. Proposed mitigation strategies include implementation of standardised transfer pathways, improved communication systems, telemedicine utilisation, and targeted enhancement of regional surgical capacity. IHT remains indispensable for accessing specialist emergency surgical care but is consistently associated with delayed treatment and worse outcomes. Addressing modifiable system factors is essential to improving safety and efficiency. These findings provide essential context for ongoing analyses of IHT practices and associated healthcare costs in regional Australia.